2019
DOI: 10.1136/bmjopen-2018-028357
|View full text |Cite
|
Sign up to set email alerts
|

Associations of school tobacco policies and legislation with youth smoking: a cross-sectional study of Danish vocational high schools

Abstract: BackgroundIn vocational high schools, the prevalence of smoking is high (nearly 40% daily smoking in Danish vocational high schools). Schools are increasingly adopting school tobacco policies (STPs) and a national law on smoke-free school grounds has been implemented. Our objective was to explore the extent of STPs in vocational schools and examine the association of STPs and smoke-free school grounds legislation with student smoking.MethodsWe used data from the cross-sectional Danish National Youth Study 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…Thus, findings from this study add to the current evidence of the potential effects of multi-component and multi-level interventions. This study indicates that smoking preventive initiatives may impact smoking decisions among adolescents and young adults at higher risk of smoking in the VET setting, which is in line with the sparse previous research in this area [ 23 , 24 ]. Meanwhile, a range of factors may have influenced the opportunities to implement intervention components as intended.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, findings from this study add to the current evidence of the potential effects of multi-component and multi-level interventions. This study indicates that smoking preventive initiatives may impact smoking decisions among adolescents and young adults at higher risk of smoking in the VET setting, which is in line with the sparse previous research in this area [ 23 , 24 ]. Meanwhile, a range of factors may have influenced the opportunities to implement intervention components as intended.…”
Section: Discussionsupporting
confidence: 89%
“…The evaluation concluded that future preventive initiatives that also included individualized efforts were necessary when addressing this group of youth. Furthermore, another study found that current smoking was lower for students attending VET schools with smoke-free school grounds, while students attending schools allowing teacher-student smoking were more likely to smoke [ 24 ]. Thus, these findings indicate that multi-level and multi-component interventions may impact VET students’ smoking behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Although more research is needed to identify potential unmeasured characteristics impacting daily smoking at 17, we are confident our results support targeted interventions among apprentices. Different smoking prevention interventions in vocational schools have been designed notably in Denmark, such as a settings-based health promotion approach through everyday school practices and school tobacco policies [47,48] and Australia via electronic feedback and referral to online and telephone services [49]. In France, the TABADO program [50] aims at encouraging apprentices to engage in a smoking cessation program.…”
Section: Discussionmentioning
confidence: 99%
“…Preventive actions in youth education settings have the potential to influence students' smoking behaviour (Andersen et al, 2019). Several studies highlight the importance of comprehensive and clear smoking bans, applicable to both students and school staff (Andersen et al, 2019;Rozema et al, 2016Rozema et al, , 2017. A smokefree environment is also associated with a reduced risk of young people taking up smoking (Egan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%